Dynamic chromatin accessibility and transcriptome changes following PDGF-BB treatment of bone-marrow derived mesenchymal stem cells - Sheng Liu; Xiaona Chu; Jill L. Reiter; Xuhong Yu; Fang Fang; Patrick McGuire; Hongyu Gao; Yunlong Liu; Jun Wan; Yue Wang (BMC Genomics, 2024)
Abstract Background Mesenchymal stem cells (MSCs) are multipotent stem cells that are under investigation for use in clinical trials because they are capable of self-renewal and differentiating into different cell types under defined conditions. Nonetheless, the therapeutic effects of MSCs have been constrained by low engraftment rates, cell fusion, and cell survival. Various strategies have been explored to improve the therapeutic efficacy of MSCs, with platelet-derived growth factor (PDGF)-BB emerging as a promising candidate. To enhance our comprehension of the impact of PDGF-BB on the gene expression profile and chromosomal accessibility of MSCs, RNA-sequencing and analysis of chromatin accessibility profiles were conducted on three human primary MSCs in culture, both with and without stimulation by PDGF-BB. Results Integrative analysis of gene expression and chromatin accessibility demonstrated that PDGF-BB treatment modified the chromatin accessibility landscape, marking regions for activation or repression through the AP-1 family transcription factors TEAD, CEBP, and RUNX2. These changes in AP-1 transcription factor expression, in turn, led to cell proliferation and differentiation potential towards osteoblasts, adipocytes, or chondrocytes. The degree of MSC differentiation varies among cells isolated from different donors. The presence of an enrichment of exosome-related genes is also noted among all the differentially expressed genes. Conclusions In conclusion, the observed changes in AP-1 transcription factor expression not only induced cellular proliferation and differentiation, but also revealed variations in the degree of MSC differentiation based on donor-specific differences. Moreover, the enrichment of exosome-related genes among differentially expressed genes suggests a potential significant role for PDGF-BB in facilitating intercellular communication.